The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1002/asi.4630370305
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between journal productivity and obsolescence

Abstract: This study examined the relationship between journal productivity and journal obsolescence for a database of references from articles dealing with desalination. Although these two variables have often been studied in isolation, no previous studies have examined their interaction within a single subject literature. It was hypothesized that those journals that were most productive would, on the average, have relatively short active lives, and that as journal productivity decreased, the average active lives of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…Some authors have downright considered growth and obsolescence inverse functions, the faster growth of literature in a field, the faster it ages and the literature becomes obsolete in a shorter time (Brookes, 1970, Egghe, 1993, Kärki and Kortelainen, 1998. Consequently, an exponential model has been proposed for the ageing of literature in the beginning, too (Wallace, 1986. In particular, the model of radioactive decay has been adopted.…”
Section: Bibliometrics Since Desolla Pricementioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have downright considered growth and obsolescence inverse functions, the faster growth of literature in a field, the faster it ages and the literature becomes obsolete in a shorter time (Brookes, 1970, Egghe, 1993, Kärki and Kortelainen, 1998. Consequently, an exponential model has been proposed for the ageing of literature in the beginning, too (Wallace, 1986. In particular, the model of radioactive decay has been adopted.…”
Section: Bibliometrics Since Desolla Pricementioning
confidence: 99%
“…First Wallace (1986) has studied ageing of scientific literature. In particular, he analysed, the relationship between journal productivity and obsolescence, and assumed an exponential distribution.…”
Section: A Model Of 'Synchronous' and The 'Diachronous' Citation Procmentioning
confidence: 99%
“…But before we do this, the next section is devoted to an apparent informetric problem raised by Wallace (1986). Wallace writes literally (p. 137): “For a given subject literature, the median citation ages of the journals contributing to that literature will vary inversely with the productivity of thoses journals, where productivity is measured in terms of the number of articles contributed by each journal.” If this is true, it would be a remarkable informetric result, useable in many other applications.…”
Section: Introductionmentioning
confidence: 99%
“… Abstract A problem, raised by Wallace (JASIS, 37, 136–145, 1986), on the relation between the journal's median citation age and its number of articles is studied. Leaving open the problem as such, we give a statistical explanation of this relationship, when replacing “median” by “mean” in Wallace's problem.…”
mentioning
confidence: 99%
“…Third, research has found that numbers of citations in core journals do not always correlate with quality papers [3,4,14,28,36]. Fourth, the development of an automated quality filtering device involves the use of so many variables that application in an information retrieval situation is essentially impractical.…”
mentioning
confidence: 99%